The Impact Covid-19 is Having on Freedom of Speech and Expression on Campuses: From Issues to Solutions - Renee Marine (Academic Chairpersons Conference Proceedings, 2022)
At a time of complete uncertainty, one thing remains consistent, the right the American people to freedom of speech and expression. What comes into question, is the cost of expressing that freedom. As stated in the First Amendment (1789): Congress shall make no law respecting an establishment of religion or prohibiting the free exercise thereof; or abridging the freedom of speech, or of the press; or the right of the people peaceably to assemble, and to petition the Government for the redress of grievances. (p. 1) Right now, while millions of people are fighting for their lives, hundreds of thousands of college students are learning what it means to have their First Amendment rights questioned. From assembly to expression to speech, students of 2020 are struggling with the growing impact of Covid-19 and their life as a student and their participation on campus. Life as normal does not exist for them, let alone anyone else, but within a generation of explorers, entrepreneurs, and risk takers, just saying ‘no,’ or ‘not to do something’ is unacceptable. This is the generation where everyone has a voice, albeit in person or social media. The simple idea of being told what to do and when to do it, when the students are so use to campus life as it was, is not a welcomed requirement. Then there are the Professors, faculty and staff of today who grew up in the 60’s, 70’s, 80’s and 90’s, and stand tall on his or her own political, societal and, culture beliefs when it comes to the pandemic. According to a reputed non-profit website of the Independence Hall Association, ushistory.org (2019), there are three legally identified free speech types: Pure speech: the verbal expression thoughts and opinions before a voluntary audience; Speech-plus: involves actions, such as demonstrating or protesting, as well as words. This type of speech is legal as long as demonstrators do not “obstruct traffic, endanger public safety, or trespass illegally; Symbolic speech: technically involves no speech at all, but it involves symbols that courts have judged as forms of free speech. (ushistory.org, 2019, p. 2) So, how is a Chair, Director, or Administrator supposed to lead during this tumultuous time? In this discussion, we will explore the issues, share solutions, and navigate expectation during this time of Covid-19. References First Amendment Rights. (1789). Retrieved from https://www.us.history.org/gov/10b/asp. ushistory.org. (2019). American Government: First Amendment Rights.
Keywords: Leadership; Covid 19; First Amendment; Free Speech; and Freedom of Expression; College and/or University